Meningkatkan Kepuasan Kerja di Perguruan Tinggi: Peran Keterbukaan Budaya, Kepemimpinan Pelayan, dan Kejenuhan Kerja - Elyzabeth Wijaya; Martin Martin; Debora Tambunan; Amin Hou; Sabaruddin Chaniago (Society, 2025)
This study explores the role of burnout as a mediating variable in the relationship between cultural openness, servant leadership, and lecturers’ job satisfaction at Institut Bisnis Informasi Teknologi dan Bisnis, Medan City. In higher education, cultural openness and servant leadership are essential factors contributing to job satisfaction. However, high workloads can lead to burnout, potentially diminishing the positive effects of both factors. This study employs a quantitative approach, using a survey conducted with 51 lecturers as respondents. The results indicate that cultural openness significantly affects job satisfaction, reinforcing the importance of transparent communication and respect for diversity in fostering a supportive work environment. Conversely, servant leadership does not significantly affect job satisfaction or burnout, suggesting that this leadership style is less effective in the context of this study. Additionally, burnout does not significantly influence job satisfaction directly or as a mediating variable. These findings underscore the need to strengthen cultural openness as a key factor in enhancing lecturer job satisfaction. Furthermore, this study offers theoretical contributions to understanding the relationship between organizational culture, leadership, burnout, and job satisfaction while providing practical insights for policy development in higher education institutions.